GEOGRAPHY OF THE MARACATU-NAÇÃO FROM PERNAMBUCO AND THE EXPANSION OF GROUPS IN BRAZIL AND WORLDWIDE (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2018)
This paper aims to present the cartography of the Maracatu-Nação (an African-Brazilian expression) and the Maracatu groups in cadastral, national and international scales and to represent by mapping geographical expansion in Brazil and in other countries. We assume that the cartography of a cultural expression is expressed through the representation of the scale of social action in the production of geographical space and has its significance, since we can highlight its concreteness through maps.